THE EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT AND QUALITY OF SERVICE PERCEIVED, IMAGE AND IMPLICATION ON CUSTOMER TRUST TO CHOOSE HOTEL STAR FOUR AND FIVE IN DKI JAKARTA - ., Mulyati (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT This study was conducted at four and five star hotels in Jakarta. The purpose of this study was to determine the effect of Customer Relationship Management and Service Quality, image individually (partial) or jointly (simultaneously) and its implications on Customer Trust Four and Five Star Hotels in Jakarta. The research problem is formulated in 7 hypotheses were tested using SEM analysis tools 8:30 LISREL program with 310 respondents, it is concluded as follows: Customer Relationship Management proved a small but not significant effect t < 2 (0.68 < 2) to Hotel image. Quality of Service perceived proved positive and significant effect on the image Hotel. Customer Relationship Management and Service Quality together proved to be a positive and significant effect on the image Hotel. Customer Relationship Management proved positive and significant effect on customer confidence. Service Quality proved positive and significant effect on customer confidence. Hotel Image proved significant influence but not t < 2 (1.06 <2) of the Customer Trust. Customer Relationship Management and Service Quality perceived and Hotel image together proved to be a positive and significant effect on customer confidence. Keywords: customer relationship management, perceived service quality, hotel image and customer trust